Microwave pyrolysis with KOH/NaOH mixture activation: A new approach to produce micro-mesoporous activated carbon for textile dye adsorption. (October 2018) - Liew, Rock Keey; Azwar, Elfina; Yek, Peter Nai Yuh; Lim, Xin Yi; Cheng, Chin Kui; Ng, Jo-Han; Jusoh, Ahmad; Lam, Wei Haur; Ibrahim, Mohd Danial; Ma, Nyuk Ling; Lam, Su Shiung
Graphical abstract: Highlights: Activated carbon (AC) was produced by microwave pyrolysis with hydroxide mixture. Four process parameters were examined for the yield and properties of AC produced. AC showed micro-mesoporous structure with high surface area and pore volume. AC showed 90% removal of malachite green dye present in textile wastewater. Activation with metal hydroxide mixture produces high-grade AC as dye adsorbent. Abstract: A micro-mesoporous activated carbon (AC) was produced via an innovative approach combining microwave pyrolysis and chemical activation using NaOH/KOH mixture. The pyrolysis was examined over different chemical impregnation ratio, microwave power, microwave irradiation time and types of activating agents for the yield, chemical composition, and porous characteristic of the AC obtained. The AC was then tested for its feasibility as textile dye adsorbent. About 29 wt% yield of AC was obtained from the banana peel with low ash and moisture (<5 wt%), and showed a micro-mesoporous structure with high BET surface area (≤1038 m 2 /g) and pore volume (≤0.80 cm 3 /g), indicating that it can be utilized as adsorbent to remove dye. Up to 90% adsorption of malachite green dye was achieved by the AC. Our results indicate that the microwave-activation approach represents a promising attempt to produce good quality AC for dye adsorption.